Ponyo [videorecording (Blu-Ray + DVD)] - Mathison, Melissa (Shout Factory, 2008)
"When Sosuke, a young boy who lives on a clifftop overlooking the sea, rescues a stranded goldfish named Ponyo, he discovers more than he bargained for. Ponyo is a curious, energetic young creature who yearns to be human, but even as she causes chaos around the house, her father, a powerful sorcerer, schemes to return Ponyo to the sea."--Container.